Heat-Up Colloidal Synthesis of Shape-Controlled Cu-Se-S Nanostructures-Role of Precursor and Surfactant Reactivity and Performance in N2 Electroreduction - Mourdikoudis, Stefanos; Antonaropoulos, George; Antonatos, Nikolas; Rosado, Marcos; Storozhuk, Liudmyla; Takahashi, Mari; Maenosono, Shinya; Luxa, Jan; Sofer, Zdeněk; Ballesteros, Belén; Thanh, Nguyen Thi Kim; Lappas, Alexandros (Nanomaterials (Basel, Switzerland), 2021)
Copper selenide-sulfide nanostructures were synthesized using metal-organic chemical routes in the presence of Cu- and Se-precursors as well as S-containing compounds. Our goal was first to examine if the initial Cu/Se 1:1 molar proportion in the starting reagents would always lead to equiatomic composition in the final product, depending on other synthesis parameters which affect the reagents reactivity. Such reaction conditions were the types of precursors, surfactants and other reagents, as well as the synthesis temperature. The use of 'hot-injection' processes was avoided, focusing on 'non-injection' ones; that is, only heat-up protocols were employed, which have the advantage of simple operation and scalability. All reagents were mixed at room temperature followed by further heating to a selected high temperature. It was found that for samples with particles of bigger size and anisotropic shape the CuSe composition was favored, whereas particles with smaller size and spherical shape possessed a Cu2-xSe phase, especially when no sulfur was present. Apart from elemental Se, Al2Se3 was used as an efficient selenium source for the first time for the acquisition of copper selenide nanostructures. The use of dodecanethiol in the presence of trioctylphosphine and elemental Se promoted the incorporation of sulfur in the materials crystal lattice, leading to Cu-Se-S compositions. A variety of techniques were used to characterize the formed nanomaterials such as XRD, TEM, HRTEM, STEM-EDX, AFM and UV-Vis-NIR. Promising results, especially for thin anisotropic nanoplates for use as electrocatalysts in nitrogen reduction reaction (NRR), were obtained.
Keywords: metal-organic chemistry; electrochemistry; copper chalcogenides; wet chemistry; morphology; nitrogen reduction reaction; bottom-up synthesis